Improving mental health literacy among young people aged 11-15 years in Java, Indonesia: co-development and feasibility testing of a culturally-appropriate, user-centred resource (IMPeTUs) - a study protocol - Helen Brooks; Irmansyah Irmansyah; Karina Lovell; Ira Savitri; Bagus Utomo; Benny Prawira; Livia Iskandar; Laoise Renwick; Rebecca Pedley; Agustin Kusumayati; Penny Bee (BMC, 2019)
Abstract Background Depression and anxiety are two of the leading causes of disease burden in low-to-middle income coutnries. The World Health Organisation has engaged in a programme of scaling-up mental health services, but significant challenges remain. Improving mental health literacy in children and young people, a core part of recent, global health strategies has the potential to address some of these challenges. The study aims to co-develop and feasibility test, a culturally-appropriate toolkit to promote depression and anxiety focused mental health literacy and self-management skills in Indonesia, for children aged 11-15 years. Methods A mixed methods study comprising four phases. Through a systematic review of existing evidence, phase 1 will review approaches to improve mental health literacy and self-management in South East Asia and critically review current evidence regarding intervention effect. Phase 2 will explore stakeholders' views on depression, anxiety and mental health more broadly and identify priorities for the intervention through the use of semi-structured interviews and/or focus groups with policy makers, clinicians, teachers, adolescent service users, carers and young people aged 11-15. Phase 3 will comprise iterative workshops with local stakeholders to present our findings and co-produce a testable, culturally appropriate toolkit to promote mental health literacy and depression/anxiety focused self-management in 11-15 year olds in Java, Indonesia. Phase 4 comprises feasibility evaluation of our developed intervention via nine in-depth case studies (Jakarta, Bogor and Magelang). We will examine the impact, acceptability and feasibility of our prototype intervention and produce evidence-based guidelines for wider implementation. Discussion Tools to support mental health literacy and self-management are a low cost way in which mental health services in LMICs can attempt to address the burden of anxiety and depression amongst children and young people. However, this is an underexplored area in Indonesia. Working closely with local stakeholders, this study will design and undertake feasibility evaluation of co-produced mental health literacy and anxiety and depression focussed interactive self-management tools. This abstract has also been published on the funders website (UK Research and Innovation. Improving Mental Health Literacy Among Young People aged 12-15 years in Indonesia 2019).